64Cu-DOTA as a surrogate positron analog of Gd-DOTA for cardiac fibrosis detection with PET: pharmacokinetic study in a rat model of chronic MI. Issue 2 (February 2016) - Kim, Heejung; Lee, Sung-Jin; Davies-Venn, Cynthia; Kim, Jin Su; Yang, Bo Yeun; Yao, Zhengsheng; Kim, Insook; Paik, Chang H.; Bluemke, David A.
Abstract : Objectives: The aim of this study was to investigate the pharmacokinetics of 64 Cu-DOTA (1, 4, 7, 10-azacyclododecane- N, N′, N′′, N′′′ -tetraacetic acid), a positron surrogate analog of the late gadolinium (Gd)-enhancement cardiac magnetic resonance agent, Gd-DOTA, in a rat model of chronic myocardial infarction (MI) and its microdistribution in the cardiac fibrosis by autoradiography. Methods: DOTA was labeled with 64 Cu-acetate. CD rats ( n =5) with MI by left anterior descending coronary artery ligation and normal rats ( n =6) were injected intravenously with 64 Cu-DOTA (18.5 MBq, 0.02 mmol DOTA/kg). Dynamic PET imaging was performed for 60 min after injection. 18 F-Fluorodeoxyglucose ([ 18 F]-FDG) PET imaging was performed to identify the viable myocardium. For the region of interest analysis, the 64 Cu-DOTA PET image was coregistered to the [ 18 F]-FDG PET image. To validate the PET images, slices of heart samples from the base to the apex were analyzed using autoradiography and by histological staining with Masson's trichrome. Results: 64 Cu-DOTA was rapidly taken up in the infarct area. The time–activity curves demonstrated that 64 Cu-DOTA concentrations in the blood, fibrotic tissue, and perfusion-rich organs peaked within a minute post injection; thereafter, it was rapidly washed out in parallel with blood clearance and excreted through the renal system. The blood clearance curve was biphasic, with a distribution half-life of less than 3 min and an elimination half-life of ∼21.8 min. The elimination half-life of 64 Cu-DOTA from the focal fibrotic tissue (∼22.4 min) and the remote myocardium (∼20.1 min) was similar to the blood elimination half-life. Consequently, the uptake ratios of focal fibrosis-to-blood and remote myocardium-to-blood remained stable for the time period between 10 and 60 min. The corresponding ratios obtained from images acquired from 30 to 60 min were 1.09 and 0.59, respectively, indicating that the concentration of 64 Cu-DOTA in the focal fibrosis was 1.85 (1.09/0.59) times greater than that in the remote myocardium. Thus, this finding indicates that the extracellular volume fraction was 1.85 times greater in the focal fibrosis than in the remote myocardium. The accumulation of 64 Cu-DOTA in fibrotic tissue was further supported by autoradiography and histology images. The autoradiography images of 64 Cu-DOTA in the fibrotic tissues were qualitatively superimposed over the histology images of the fibrotic tissues. The histology images of the infarct areas were characterized by a heterogeneous distribution of thin bands of fibrotic collagen, myocytes, and expanded extracellular space. Conclusion: 64 Cu-DOTA is a useful surrogate positron analog of Gd-DOTA, enabling quantitative measurement of the uptake values in fibrotic tissues by dynamic PET imaging and calculation of the extracellular volume fractions of the fibrotic tissues. At a microscopic level, the distribution of 64 Cu-DOTA is nonuniform, corresponding to the heterogeneous distribution of expanded extracellular space in the setting of MI.